Institutional Dimension of Sustainability and Environmental Management in the municipality of Moju, Pará:: an application of the Barometer of Sustainability - Cardoso, Andreza Soares; Toledo, Peter Mann de; Vieira, Ima Célia Guimarães (Sustainability in Debate, 2014)
Few analytical tools have been applied in sustainability studies in Amazonia, especially in the State of Pará. Municipalities in Pará included in the Centers for Biodiesel Production program of the Brazilian government, particularly Moju, are undergoing a phase of intensive agroindustrial investment for the production of Oil Palm, and of firm insertion of family agriculture in such a process. In this context, questions have arisen about the ability of Moju in absorbing such a public policy, represented by new territorial dynamics and which require strong local capacity of environmental management. This research aims to evaluate the institutional dimension of sustainability of the municipality of Moju by verifying the conditions presented by the city council vis-Ã -vis environmental management. We used the Barometer of Sustainability (BS) for this analysis, taking into account five themes (institutional structure, operational structure, terms of conduct adjustment, rural environmental register and landholding tenure) and 33 indicators, complemented by interviews with local administrators and entrepreneurs. Results revealed that Moju is indeed equipped for full environmental management, but also that this operational structure is still inadequate, which should certainly bring out problems if this policy is put into effect.